REVITALIZING OLD PUMPING STATIONS: STRATEGIES FOR ENERGY SAVINGS - Ahmedov Durbek Madaminjon o’g’li; Mehmonaliyev Mehriddin (TADQIQOTLAR.UZ, 2024)
Abstract: Energy efficiency is a critical concern in modern infrastructure management, particularly in aging pumping stations. These facilities play a pivotal role in water distribution and management systems but often suffer from inefficiencies due to outdated equipment and design. This paper explores various strategies to achieve energy savings in old pumping stations. By employing innovative technologies, optimizing operational procedures, and implementing systematic maintenance practices, significant reductions in energy consumption can be attained while ensuring the reliability and functionality of these essential assets. This article discusses practical approaches and case studies to demonstrate the feasibility and benefits of energy- saving initiatives in revitalizing aging pumping stations.